Extension of Dancer’s Legs: Increasing Angles Show Motion - Mastandrea, Stefano; Kennedy, John M. (Frontiers in Psychology, 2022)
Usain Bolt’s Lightning Bolt pose, one arm highly extended to one side, suggests action. Likewise, static pictures of animals, legs extended, show animation. We tested a new cue for motion perception -extension- and in particular extension of dancer’s legs. An experiment with pictures of a dancer finds larger angles between the legs suggest greater movement, especially with in-air poses and in lateral views. Leg positions graded from simply standing to very difficult front and side splits. Liking ratings (a small range) were more related to Difficulty ratings (a large range) than Movement ratings (a moderate range).